2020
DOI: 10.1021/acs.nanolett.0c02973
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Nanochannels Connected in Series for Dynamic Control of Multiple Concentration-Polarization Layers and Preconcentrated Molecule Plugs

Abstract: Integration of ionic permselective medium (e.g., nanochannels, membranes) within microfluidic channels has been shown to enable on-chip desalination, sample purification, bioparticle sorting, and biomolecule concentration for enhanced detection sensitivity. However, the ion-permselective mediums are generally of fixed properties and cannot be dynamically tuned. Here we study a microfluidic device consisting of an array of individually addressable elastic membranes connected in series on top of a single microfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…Of note, the cross-section reconstruction and the particle trajectories suggested that starting from 18 psi, the ceiling of the main microchannel underneath the microvalve had already partially collapsed onto the bottom surface at the center of the main channel while leaving gaps only at the sides of the microchannel cross-section. The partial contact between the ceiling and the bottom surfaces of the microchannel may have resulted in the formation of nanochannels. However, the contribution of these nanochannels to the developed ICP was ruled out by repeating the same experiments in an identical microchannel system without a CEM coating. Even for the maximum tested P (32 psi), there was no indication of ICP, likely due to lack of ionic permselectivity of the obtained nanochannels at this relatively strong electrolyte ionic strength (∼10 mM) [Figure S9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the cross-section reconstruction and the particle trajectories suggested that starting from 18 psi, the ceiling of the main microchannel underneath the microvalve had already partially collapsed onto the bottom surface at the center of the main channel while leaving gaps only at the sides of the microchannel cross-section. The partial contact between the ceiling and the bottom surfaces of the microchannel may have resulted in the formation of nanochannels. However, the contribution of these nanochannels to the developed ICP was ruled out by repeating the same experiments in an identical microchannel system without a CEM coating. Even for the maximum tested P (32 psi), there was no indication of ICP, likely due to lack of ionic permselectivity of the obtained nanochannels at this relatively strong electrolyte ionic strength (∼10 mM) [Figure S9].…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we developed a series of tunable nanochannels by using microvalves made of a soft elastomer (polydimethylsiloxane, PDMS) . Each microvalve enables tuning of the cross-sectional area of the main microchannel from the micro- to nano-meter scale, thereby switching the microchannel into an ionic permselective nanochannel. It was shown that a series of such tunable nanochannels can be used to generate multiple plugs in series, wherein the location of the multiple plugs can be dynamically controlled based on which microvalves were operated. However, the fact that the solution must flow through nanochannels with high hydrodynamic resistances results in a low throughput and correspondingly prolonged process, with a low preconcentration factor.…”
Section: Introductionmentioning
confidence: 99%
“…They constitute the emerging research field known as iontronics. Iontronic devices usually contain nanometer-sized fluidic structures (e.g., nanochannels, ion exchange membranes) that exhibit ion permselectivity due to the overlap of their electric double layers (EDLs) . Their unique electrical behavior enables them to perform in vitro/vivo information processing at the ionic level using iontronic components such as resistors, diodes, capacitors, and transistors. ,, These nanofluidic components are attracting intensive study, given their fundamental interest and promising applications beyond biomimetic information processing that can contribute to improving chemical and biochemical sensing, , such as for energy harvesting, single molecule detection, electrokinetic preconcentration, , and brain–machine interfaces . Some of the best-known electrical gates for Boolean logic computation consist of diodes, i.e., diode-based logic gates (DLGs).…”
Section: Introductionmentioning
confidence: 99%
“…One approach to achieve direct control over the length of the depletion layer, which in turn controls the location of the preconcentrated plug, uses either embedded electrodes or heaters for local stirring of the fluid, which respectively induce alternating-current-electro-osmosis (ACEO) 25 or electro-thermal (ET) flow. 26 Another approach to control the location of a single preconcentrated plug is to use two ion-permselective membranes 27–29 or nanochannels 30 in series. It has been shown that in the intermediate region between the two membranes, the enriched layer prevents propagation of the depletion layer and its corresponding developed preconcentrated molecule plug.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in the intermediate region between the two membranes, the enriched layer prevents propagation of the depletion layer and its corresponding developed preconcentrated molecule plug. 27–30 While being able to control the location of a preconcentrated biomolecule plug, these approaches are limited to a single plug from a single source ( i.e. inlet) within a straight microchannel.…”
Section: Introductionmentioning
confidence: 99%